Relationship of Anthropometric Indices of Body Fat to Cardiovascular Risk in Japanese Women - KOIMIYA, Shuichi; IMAI, Katsumi; MASUDA, Takashi (Annals of physiological anthropology, 1993)
The relationship between body fat indices and cardiovascular risk was analyzed in 97 Japanese women aged 36-72 years. The variables used were anthropometric measures of body fatness, blood lipids and blood pressure. Total adipose tissue weight (TATW) was estimated from bioelectrical impedance measurements. Subcutaneous adipose tissue weight (SATW) was calculated by measuring subcutaneous fat thickness at I4 sites using a skinfold caliper. The indices of body fat distribution were the ratios of waist to hip circumference (WHR) and abdominal to hip circumference (AHR). Blood pressure and serum lipid levels were determined in all subjects after an overnight fast. The correlations among the various body fat indices were high, and all were strongly correlated with WHR and AHR ; only %SATW and percent-age internal adipose tissue weight (%TATW) were not correlated with WHR and AHR.